Los hábitos alimenticios y su incidencia en el rendimiento académico de los estudiantes de 2º y 3º grado de E.G.B. del Comil n° 13 Patria, parroquia Guaytacama, cantón Latacunga, en el año lectivo 2014-2015 - Molina Herrera, Silvana Margoth (2015)
This research has as main objective to provide alternative solutions to the problem of lack of food habits and their impact on the academic performance of children. Methods of investigation as the inductive-deductive, which made it possible to diagnose the problem was used to solve the problem; the type of research corresponds to the description that places the problem in a general context. Finally the collection of information is used by the survey technique for application it was necessary to apply the same survey was directed to parents and teachers of the institution under study. The results were subjected to statistical processes for analysis and interpretation. The validity and reliability is determined by the judgment of experts, mainly from the critical analysis of the research, which was reached acceptable reliability. The conclusions and recommendations that supported the proposal were established, thus enabling the development of a food guide to improve the academic performance of students in 2nd and 3ºgradothe beneficiaries are students COMIL No. 13 "Patria" with the implementation of the proposal will significantly contribute to improved academic performance.